ANÁLISE DE UM EVENTO SINGULAR DE INTERAÇÃO MÃE-CRIANÇA NA CONSTITUIÇÃO DE UM SENTIDO PARA A ESCRITA - Mayrink-Sabinson, Maria Laura (Organon, 2012)
In this paper, which shares the theoretical and methodological assumptions of theIntegrated Project CNPq “The theoretical relevance of singular data in the acquisition ofwritten language”, a singular event of mother and pre-school child interaction is analysed asto the way adult and child act in constituting meaning to writing with the objetive of discussingthe theoretical status to be attributed to the OTHER/interlocutor in the process of writtenlanguage acquisition. The analysis shows that the SUBJECT/OTHER is in constant movementbe it a child in search of authonomy or a literate adult. It also shows that the movement of theSUBJECT/OTHER affects the movement of the OTHER/SUBJECT whom he encounters andwith whom he confronts in the process of interlocution. Theories which aim to explain theprocess of written language acquisition should not only attribute a constitutive role to theOTHER/interlocutor but also allow an explanation of this movement of reciprocal constitution.